Pengaruh Kompetensi Pedagogik Guru Pendidikan Agama Kristen terhadap Keaktifan Belajar Siswa Kelas XI SMA Negeri 2 Tarutung, Kabupaten Tapanuli Utara Tahun Pembelajaran 2024/2025 - Henni Jannimar Sonya Sitompul; Simion D. Harianja; Tiur Imeldawati; Lasmaria Lumban Tobing; Ronny Simatupang (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The purpose of this study was to determine the positive and significant influence of the pedagogical competence of Christian Religious Education teachers on the learning activity of class XI students of SMA Negeri 2 Tarutung, North Tapanuli Regency in the 2024/2025 academic year. The method used in this study is a quantitative descriptive inferential method. The population was all class XI students of SMA Negeri 2 Tarutung totaling 274 students and a sample of 35 people was determined using Purposive Sampling. Data were collected with a closed questionnaire of 34 items. The results of the data analysis showed that there was a positive and significant influence of the Pedagogical Competence of Christian Religious Education Teachers on the Learning Activity of Class XI Students of SMA Negeri 2 Tarutung, North Tapanuli Regency in the 2024/2025 Academic Year, as evidenced by the following data analysis: 1) Analysis requirements test: a) a positive relationship test obtained a value of rxy = 0.619> rtable ( = 0.05, n = 35) = 0.334. b) Test of significant relationship obtained tcount value = 4.524 > ttable ( = 0.05, dk = n-2 = 33) = 2.042. 2) Test of influence: a) Test of regression equation, obtained regression equation Y ̂="16.36" + 0.65X. b) Test of regression determination coefficient (r2) = 38.3%. 3) Hypothesis test using F test obtained Fcount > Ftable = ( = 0.05, dk numerator k = 21, dk denominator = n-2 = 35-2 = 33) which is 20.43 > 1.62. Thus Ha is accepted and H0 is rejected.